2020
DOI: 10.1108/ijmpb-02-2020-0058
|View full text |Cite
|
Sign up to set email alerts
|

Organizational flexibility and project portfolio performance: the roles of innovation, absorptive capacity and environmental dynamism

Abstract: PurposeThe aim of the current study is to empirically assess the effects of organizational flexibility on project portfolio (PP) performance, with the mediating role of innovation and moderating effects of environmental dynamism (ED) and absorptive capability (AC).Design/methodology/approachData were collected from 173 manufacturing firms and analyzed using structural equation modeling (SEM) with the help of a partial least squares (PLS) approach.FindingsResults show that innovation partially mediates the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 102 publications
0
12
0
Order By: Relevance
“…Besides, the findings of this study show that OF is conducive to promoting TI and MI. OF generates creativity [53], allowing the firm to develop new products or services and make adjustments in management regulation, process, and method to adapt to market demands quickly [9]. Furthermore, previous studies demonstrated that the dimensions of organizational flexibility that are established in this paper (SF/RF/LF/CF/TF/IF) can positively promote OI.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Besides, the findings of this study show that OF is conducive to promoting TI and MI. OF generates creativity [53], allowing the firm to develop new products or services and make adjustments in management regulation, process, and method to adapt to market demands quickly [9]. Furthermore, previous studies demonstrated that the dimensions of organizational flexibility that are established in this paper (SF/RF/LF/CF/TF/IF) can positively promote OI.…”
mentioning
confidence: 71%
“…Thanks to flexibility, firms can react to environmental changes and uncertainties more quickly: They can absorb change, integrate, develop, and restructure resources and capabilities in the organization in a short time [8]. Besides, improving flexibility is considered a crucial tool that can predict organizational performance [9]. Therefore, enhancing flexibility serves as a feasible solution for promotion of enterprise competitiveness in a turbulent environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other scholars have suggested working with AC as a moderating factor. For instance, Saeed et al (2021) analyzed AC through innovation and project portfolio. Furthermore, Ahlin et al (2014) explored AC through entrepreneurs' networks and product and process innovation.…”
Section: 4mentioning
confidence: 99%
“…The search for better results requires companies to constantly improve management models used and techniques adopted (Carvalho et al , 2015; Saeed et al , 2020). To ensure good organizational performance, it is necessary to invest in new approaches, manage the costs, improve existing management tools, understand customers' requirements and constantly innovate responsibly and sustainably (Sanchez et al , 2017).…”
Section: Introductionmentioning
confidence: 99%